Optimización del sistema de tratamiento fisicoquímico de una estación depuradora de aguas residuales de bebidas gaseosas - Ordóñez Ramírez, Virgilio Alonso (2020)
This study makes it possible to resolve a serious environmental-economic problem that affects the community, caused by treatment plants with low levels of efficiency and high operating costs due to the excessive addition of reagents. After applied and experimental research, a diagnosis was made to determine the maintenance requirements, the identification of the concentrations and the exact point where solutions needed for wastewater treatment should be added. The results obtained establish that the ideal dosage of aluminum sulfate for maximizing the contaminant removal efficiency in the treatment plant at a value greater than 90% was 250 ppm.